2017
DOI: 10.1016/j.jcmg.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Mid-Term Outcomes of Possible Leaflet Thrombosis After TAVR

Abstract: HALT with reduced leaflet motion was not rare but usually subclinical. Valve hemodynamics and mid-term outcomes were uneventful even without additional anticoagulant therapy in our limited number of cases. Male sex, larger sinus and bioprosthesis size, and elevated D-dimer levels during follow-up were associated with this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 25 publications
6
105
1
4
Order By: Relevance
“…However, HALT and RLM were noted in patients receiving ongoing anticoagulation therapy, indicating that anticoagulation therapy is not a guarantee against these phenomena. This finding is supported by findings of a recent larger series of bioprosthetic valves …”
Section: Discussionsupporting
confidence: 86%
“…However, HALT and RLM were noted in patients receiving ongoing anticoagulation therapy, indicating that anticoagulation therapy is not a guarantee against these phenomena. This finding is supported by findings of a recent larger series of bioprosthetic valves …”
Section: Discussionsupporting
confidence: 86%
“…Pressure differences naturally increase as the valve opening becomes more limited; one study reported that 16% of patients who were asymptomatic but had reduced leaflet motion on CT had a peak pressure difference of 20 mm Hg or greater 14. However, there are some cases where echocardiography does not demonstrate any significant increase in valvular pressure difference 4. Yanagisawa et al reported that the D-dimer level was significantly higher in a group of patients with HALT observed 6 months postoperatively than in the group without (2.3 vs 1.1 mg/mL, p=0.002) 4.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…However, there are some cases where echocardiography does not demonstrate any significant increase in valvular pressure difference 4. Yanagisawa et al reported that the D-dimer level was significantly higher in a group of patients with HALT observed 6 months postoperatively than in the group without (2.3 vs 1.1 mg/mL, p=0.002) 4. Elevated D-dimer levels may serve as a reference indicator in cases of suspected HALT.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaflet thrombosis in particular can be identified with Computed Tomography (CT) imaging 5, 6 . Many in-vivo clinical studies have tried to identify possible causes leading to leaflet thrombosis such as retention of blood flow and stasis in the sinuses and at the base of the leaflets 79 , lower implants of TAVs 7, 8 , under-expansion and asymmetry of the TAV 8 , incomplete TAV apposition to the aortic wall 9, 10 , the metallic frame of the TAV 9, 10 and other conditions.…”
Section: Introductionmentioning
confidence: 99%